The development of the “Bawi Kuwu” learning model in the text writing material of the observation report - Indra Perdana (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The application of the learning model is an operational step to achieving maximum learning goals. Based on the results of the author's observation on Indonesian Language subjects, especially in the field of writing skills, the Report on Observation Results (LHO) is often found to be a problem, students find it difficult to make sentences and paragraphs of LHO text. This is because the teacher often implements an inappropriate learning model, so students have not been able to fully understand the concept of the LHO text. The selection of creative and innovative learning methods and models can influence the ability of students to construct their knowledge well. The application of creative and innovative learning models can also be developed from a local wisdom in each region, for example the local wisdom of Bawi Kuwu folklore in Central Kalimantan. Folklore Bawi Kuwu can be modified into a learning model by paying attention to the cultural value of the story. The Bawi Kuwu (BK) learning model is a group learning model based on the cultural value of folklore in Central Kalimantan and the collaboration between the concept of cooperative jigsaw learning models and peer teaching. The application of the Bawi Kuwu learning pattern in writing the Observation Results Text is very suitable to be applied because in its application the students in the group try to construct their knowledge and convey it to a student in his group with the guidance of the teacher.